2023
DOI: 10.1128/msphere.00263-22
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Mexican Free-Tailed Bats ( Tadarida brasiliensis ) with SARS-CoV-2

Abstract: As the COVID-19 pandemic has continued for 3+ years, there has been increasing concern that the SARS-CoV-2 virus will enter wildlife populations and potentially create new reservoirs where the virus could adapt to a new host and create variants. This is particularly possible with species that reside in man-made structures, in proximity to infected human populations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…More recently, two studies looking at the susceptibility of the Brazilian free-tailed bat showed that the species can become infected (without showing symptoms) and develop antibodies to SC2. However, both studies found no evidence of viral transmission to uninfected bats (26,27). Our results correlate with these findings as the Brazilian free-tailed bat ACE2 cell line was able to replicate all three variants of SC2 (Figures 3-5).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More recently, two studies looking at the susceptibility of the Brazilian free-tailed bat showed that the species can become infected (without showing symptoms) and develop antibodies to SC2. However, both studies found no evidence of viral transmission to uninfected bats (26,27). Our results correlate with these findings as the Brazilian free-tailed bat ACE2 cell line was able to replicate all three variants of SC2 (Figures 3-5).…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that bat-borne SC2-like viruses circulate in Rhinolophus species in Southeast Asia, but a direct progenitor virus has yet to be found (25). To date, only four bat species have been experimentally infected with SC2, whereas roughly 1400 species of bats are estimated worldwide (26)(27)(28)(29). To test susceptibility of every bat species to SC2 would be impractical, but less intrusive and lower-cost methods are available to examine if the virus can replicate within a bat species.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental challenge of Egyptian fruit bats led to a limited infection without visible signs of disease, but with detectable virus in several tissues, including lungs and lymph nodes, and transmission to one contact bat (28). Challenge of big brown bats did not lead to infection (29); however, two studies of Mexican/Brazilian free-tail bats were contradictory, with one suggesting they were susceptible but not the other (30, 31). ACE2 residues that are thought to be important in SARS-CoV-2 spike binding (38, 39) are more conserved in Egyptian fruit bats (16/20 residues with human), substantially less in big brown bats and Mexican/Brazilian free-tailed bats (11/20 residues), with Jamaican fruit bats intermediate (13/20 residues) (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, insectivorous bats are typically captured and used for one-off experimental infection studies. Despite these limitations, previous work using Egyptian fruit bats ( Rousettus aegyptiacus ), and insectivorous big brown ( Eptesicus fuscus ) and Brazilian/Mexican free-tailed ( Tadarida brasiliensis ) bats have examined susceptibility to SARS-CoV-2 infections (2831). Although Egyptian fruit bats were moderately susceptible without disease, with detection of virus in the respiratory tract for several days and transmission to one other bat, big brown bats were not susceptible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation